DEVELOPMENT MODEL OF TRANSMIGRATION AREA BASED ON LEADING COMMODITIES IN MUARA KOMAM SUB-DISTRICT - Buchari, Ahmad; Muhammad Iftitah Sulaiman Suryanagara; Niken Nurmiyati; Hirzi Fathul Hakim; Iqbal Saputra Zana (Journal of Indonesian Rural and Regional Government, 2025)
This study aims to formulate a development model for transmigration areas based on superior commodities in Muara Komam District, Paser Regency, East Kalimantan. The research employs a descriptive qualitative method, using data from document analysis, in-depth interviews, and focus group discussions with local stakeholders, and analyzes official government documents to map the existing superior commodities. The findings indicate that strengthening key commodities, such as horticulture, perennial fruits, biopharmaceutical plants, and livestock, is a major driver of economic growth and improved welfare among transmigrant communities. The proposed development model adopts spatial, regional economic, infrastructure, investment, and area management approaches, integrating an agropolitan system and regional economic networks as the main development drivers. Community-based development is identified as a key element for maintaining the region’s socio-economic sustainability through active participation, agricultural innovation, and equitable resource management. The study recommends policy directions that emphasize synergy among government, investment, and community actors to establish a self-reliant, competitive, and sustainable transmigration area in Muara Komam.